Singular Integral Equation for Curved Cracks - Nik Long, Nik Mohd Asri; Eshkuvatov, Zainiddin K. (Institute for Mathematical Research, 2008)
The complex potential method is used to formulate singular integral equation for the curved crack problem in plane elasticity. This equation describes the relation of the displacement jump versus the resultant force applied along the crack face.